YWCA Building, Panama-Pacific International Exposition, first floor plan, 1914 - Julia Morgan::::::::: (1914)
See 010-7-c-ff059-02-02 for another copy of the drawing, with different annotations and added lines. Note on the drawing reads: 'Exterior design is furnished by the P.P.I.E Co. The work of Edward F. Champney and is same as for press building.'